Ultimate veg ebook Easy & delicious meals for everyone [american measurements]. - Oliver, Jamie (2020)
NEW YORK TIMES BESTSELLER Jamie Oliver, one of the bestselling cookbook authors of all time, is back with brilliantly easy, delicious, and flavor-packed vegetable recipes. This edition has been adapted for the US market. It was originally published in the UK under the title Veg . From simple suppers and family favorites, to weekend dishes for sharing with friends, this book is packed full of phenomenal food - pure and simple. Whether it's embracing a meat-free day or two each week, living a vegetarian lifestyle, or just wanting to try some brilliant new flavor combinations, this book ticks all the boxes. Super-tasty, brilliantly simple, but inventive veg dishes include: · AMAZING VEGGIE CHILI , comforting black rice, zingy crunchy salsa and chili-rippled yogurt · GREENS MAC 'N' CHEESE with leek, broccoli & spinach and a toasted almond topping · VEGGIE PAD THAI , crispy fried eggs, special tamarind & tofu sauce and peanut sprinkle · SUPER SPINACH PANCAKES with avocado, tomato and cottage cheese · SUMMER TAGLIATELLE , basil & almond pesto, broken potatoes and delicate green veg With chapters on Soups & Sandwiches, Brunch, Pies & Bakes, Curries & Stews, Salads, Burgers & Fritters, Pasta, Rice & Noodles, and Traybakes there's something tasty for every occasion. Sharing simple tips and tricks that will excite the taste buds, this book will give you the confidence to up your vegetable intake and widen your recipe repertoire, safe in the knowledge that it'll taste utterly delicious. It will also leave you feeling full, satisfied and happy - and not missing meat from your plate. "It's all about celebrating really good, tasty food that just happens to be meat-free." Jamie Oliver